Talking Modules to Promote Oral Hygiene and Hand Washing Habits (Docentes 2.0 Journal, 2021)
Dental caries has a high prevalence; it is prevented with oral hygiene measures; The present teachers practice tooth brushing and hand hygiene to define the basic behaviors of their health in the young students in the future. This research aimed to design two speaking modules to support practices on oral hygiene and handwashing habits in teachers of an intercultural center in Bogotá during 2020. Qualitative research was carried out, with a sample not probabilistic, homogeneous, of 8 teachers responsible for teaching children from urban indigenous ethnic groups. An unstructured interview was used as a technique; subsequently, content analysis was made of the sentences transcribed verbatim in the responses as a basis for proposing a support didactic tool mediated by information and communication technologies to encourage healthy habits. They were considering the intercultural context to predict the results in the medium and long term. The definition of mouth and hands from the anatomical point of view was found in the teachers and their use for everyday life, serving personal development. The teachers proposed two speaking modules in the dialect of the ethnic groups of the children from the intercultural center. The teachers' understanding of oral health and handwashing made it possible to jointly propose two talking modules to promote oral hygiene and handwashing habits and thus facilitate communication and collaboration in the design of learning environments, where gives voice and involves groups of people, related to this activity.
Keywords: Oral hygiene; hand washing; modules